TRIM10 binds to IFN‐α/β receptor 1 to negatively regulate type I IFN signal transduction - Guo, Mengmeng; Cao, Wenyan; Chen, Shengwen; Tian, Renyun; Wang, Luoling; Liu, Qian; Zhang, Lini; Wang, Zhenghao; Zhao, Ming; Lu, Qianjin; Zhu, Haizhen (European journal of immunology, 2021)
The type I interferon (IFN‐I) system is important for antiviral and anticancer immunity. Prolonged activation of IFN/JAK/STAT signaling is closely associated with autoimmune diseases. TRIM10 dysfunction may be associated closely with certain autoimmune disorders. Here, we observed that the serum TRIM10 protein level is lower in patients with systemic lupus erythematosus than in healthy control subjects. We speculated the possible involvement of TRIM10‐induced modulation of the IFN/JAK/STAT signaling pathway in systemic lupus erythematosus. In line with our hypothesis, TRIM10 inhibited the activation of JAK/STAT signaling pathway triggered by various stimuli. TRIM10 restricted the IFN‐I/JAK/STAT signaling pathway, which was independent of its E3 ligase activity. Mechanistically, TRIM10 interacted with the intracellular domain of IFNAR1 and blocked the association of IFNAR1 with TYK2. These data suggest the possible TRIM10 suppresses IFN/JAK/STAT signaling pathway through blocking the interaction between IFNAR1 and TYK2. Targeting TRIM10 is a potential strategy for treating autoimmune diseases. TRIM10 interacts with IFNAR1 and block the interaction between IFNAR1 and TYK2, inhibiting the expression of downstream ISGs in the type I IFN signaling pathway. Serum TRIM10 is low in the patients with systemic lupus erythematosus, suggesting TRIM10 may be involved in SLE pathogenesis.